QUALITY OF WORK LIFE, ORGANIZATIONAL COMMITMENT AND TURNOVER INTENTION IN ACCOUNT OFFICER OF MICRO FINANCE COMPANY - Adinna Astrianti; Mukhamad Najib; Bagus Sartono (Universitas Padjadjaran, 2020)
The purpose of this study is to analyze the effect of quality of work life (QWL) on turnover intention through organizational commitment of account officers in micro-finance company. This research was conducted using the survey method. Data were collected using questionnaires from 115 account officers at a micro-finance company in West Java. Data were analyzed using descriptive statistics and SEM-PLS. The results of this study indicate that QWL has a significant and positive effect on organizational commitment and organizational commitment has a significant and negative effect on turnover intention. It can be concluded that by increasing the implementation of QWL will increase the organizational commitment of employees to remain in the company so that it decreases the intention of employees to move or leave the company.